Chinese ethnomusicology to explore fieldwork methods - Fan Lihan (SHS Web of Conferences, 2016)
The main working approach and scope of the national musicians is the field investigation. The exploration of successful experience of the Chinese national music in the fieldwork is very necessary to effectively organize, carry out and complete the fieldwork of the Chinese music. This paper which is combined with the summary of experience, expert consultation and literature reading tries to verify and promote the effective fieldwork method through field investigation, so as to avoid that the national musicians with curiosity give a hurried and cursory glance at the destination and miss the first-hand resources in the field investigation due to lack of effective working approach, which plays a positive role in the inheritance and development of the Chinese national music.